2019
DOI: 10.1051/0004-6361/201935952
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the 16 Cygni planet host at unprecedented precision and exploring automated tools for precise abundances

Abstract: The binary system 16 Cygni is key in studies of the planet-star chemical composition connection, as only one of the stars is known to host a planet. This allows us to better assess the possible influence of planet interactions on the chemical composition of stars that are born from the same cloud and thus should have a similar abundance pattern. In our previous work, we found clear abundance differences for elements with Z ≤ 30 between both components of this system and a trend of these abundances as a functio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(27 citation statements)
references
References 92 publications
(137 reference statements)
3
24
0
Order By: Relevance
“…This, and more sophisticated diagnostics for additional modes, was used by Bellinger et al (2017) to find an asteroseismic estimate of τ ¼ 6.9 AE 0.4 Gyr. This is in excellent agreement with other methods for this well-characterized bright exoplanet host binary (Maia et al, 2019). The similarity of the nonradial oscillations of 16 Cyg A to those of the Sun as illustrated in Fig.…”
Section: Asymptotic Representations Of High-order Modessupporting
confidence: 90%
“…This, and more sophisticated diagnostics for additional modes, was used by Bellinger et al (2017) to find an asteroseismic estimate of τ ¼ 6.9 AE 0.4 Gyr. This is in excellent agreement with other methods for this well-characterized bright exoplanet host binary (Maia et al, 2019). The similarity of the nonradial oscillations of 16 Cyg A to those of the Sun as illustrated in Fig.…”
Section: Asymptotic Representations Of High-order Modessupporting
confidence: 90%
“…Despite the difference in the mass of the binary components being only ∼0.05 M ⊙ , King et al (1997) found that 16 Cyg A has a much larger Li abundance (∼0.67 dex) than 16 Cyg B. This result has been recently confirmed using superb HDS/Subaru spectra with R = 160,000 and S / N = 1,000 by Maia et al (2019), who find that 16 Cyg A has an Li abundance 0.70 dex larger than 16 Cyg B (see also Gonzalez 1998; Ramírez et al 2011). This large difference could be due to the engulfment of planetary material by 16 Cyg A, which has an Li abundance larger than expected for its age (Carlos et al 2016).…”
Section: And Be In Solar Twin Binariesmentioning
confidence: 86%
“…Regarding Be, as discussed in the previous section, it is less affected by depletion than Li, and indeed, previous studies found comparable Be abundances between both components (Deliyannis et al 2000; Garcia Lopez & Perez de Taoro 1998; Takeda et al 2011). The most precise study by Maia et al (2019) found that Be is about 0.07 dex higher in 16 Cyg A than in 16 Cyg B. As Be is a refractory element (Lodders 2003), it is expected that the ingestion of planetary material will also increase Be, as observed.…”
Section: And Be In Solar Twin Binariesmentioning
confidence: 87%
See 1 more Smart Citation
“…The abundance patterns (versus condensation temperature) found by Meléndez et al (2009Meléndez et al ( , 2017; Oh et al (2018); Maia et al (2019); Ramírez et al (2019) and Saffe et al (2015) in solar twins and twin-star binary systems have been linked to the formation of planets (for an alternative explanation regarding dust cleansing, see Gustafsson 2018a,b). In particular, it is argued that the formation of rocky planets removes refractory elements from the hosted star.…”
Section: Planet Engulfmentmentioning
confidence: 99%

Rocky planet engulfment in the binary system HIP 71726-37

Galarza,
López-Valdivia,
Meléndez
et al. 2021
Preprint
Self Cite